2012
DOI: 10.1021/ef301433m
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Cation and Salinity Effect on Electrocoalescence of Water/Crude Oil Emulsions

Abstract: The resolution of water-in-crude oil (W/O) emulsions formed during extraction or desalinaton processes of crude oil is still a problem for the oil industry. Among the main separation processes used today, electrostatic separation induced by the application of DC or AC electric fields is the most interesting because it is ecologically correct. However, the electroseparation efficiency is still limited by the current lack of knowledge concerning the mechanism that is behind this process. Stabilization of the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Perles and colleagues [71] applied the rheology method and explained this contrast by concluding that the presence of salt improves W/O emulsion stability up to a critical ionic strength value (~ 0.1-0.3 mol L -1 ) above which its stability is diminished. On the other hand, electro-rheological investigations proved that W/O emulsions with water phase containing divalent cation (Ca 2+ or Ba 2+ ) are more stable than those with aqueous phase composed of monovalent cation (Na + or K + ) [70,71].…”
Section: Salinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Perles and colleagues [71] applied the rheology method and explained this contrast by concluding that the presence of salt improves W/O emulsion stability up to a critical ionic strength value (~ 0.1-0.3 mol L -1 ) above which its stability is diminished. On the other hand, electro-rheological investigations proved that W/O emulsions with water phase containing divalent cation (Ca 2+ or Ba 2+ ) are more stable than those with aqueous phase composed of monovalent cation (Na + or K + ) [70,71].…”
Section: Salinitymentioning
confidence: 99%
“…Perles and colleagues [71] applied the rheology method and explained this contrast by concluding that the presence of salt improves W/O emulsion stability up to a critical ionic strength value (~ 0.1-0.3 mol L -1 ) above which its stability is diminished. On the other hand, electro-rheological investigations proved that W/O emulsions with water phase containing divalent cation (Ca 2+ or Ba 2+ ) are more stable than those with aqueous phase composed of monovalent cation (Na + or K + ) [70,71]. On the contrary, the presence of salts with divalent cation raises demulsification competence of O/W emulsion to a greater extent than that with monovalent cation, which is probably assigned to the lesser hydrophilicity of the former [3,14,72].…”
Section: Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in terms of emulsion droplet size, it was observed that significant reduction in emulsion sizes take place at lower salinities (Moradi et al 2011). They also demonstrated that the stability of the emulsions formed in an aqueous environment saturated with divalent ions (Ca ++ ) differs from monovalent (Na + ) systems (Wang andAlvarado 2012 andPerles et al 2012). However, it should be pointed out that they deliberately agitated oil and brine to form the emulsions whereas in our case, the observed microdispersions form spontaneously when a crude oil contacts low salinity brines.…”
Section: Introductionmentioning
confidence: 95%
“…However, this hardware has considerable volume as well as expensive to install on offshore platforms [155]. Electrical demulsification is generally considered advantageous from the perspective of energy consumption as compared with other demulsification approaches, such as heating or centrifugation, in addition to ecological validity [156,157]. However, the drawback of this process is the formation of fine secondary droplets during the coalescence, making it more burdensome to separate the produced smaller water drops [158].…”
Section: The Advantages and Disadvantages Of Some Demulsification Tecmentioning
confidence: 99%